Les particulariteś de la technique narative dans „Le page disgracié” de T.L’Hermite (Literatures of the World: Poetics, Mentality and Spirituality, 2020)
The article deals with the features of narrative technology in Tristan l'Hermite’s novel Le Page disgracié (1643; “The Disgraced Page”). The genre nature of the work remains uncertain. The intertwining of autobiography with well-known literary models generates a great deal of heated debates in the scientific community. The author's narrative strategy is currently poorly understood, but it is precisely this that can clarify the artistic nature of the work. The author uses different spheres of novel understanding of reality, using personal, individual experience, trying to bring the novel’s world closer to reality. The combination of elements of different novel poetics and innovations in the narrative structure are the important steps in the development of the genre of novels in a historical perspective.
Keywords: romanticized autobiography; picaresque novel; pastoral; fabliau; burlesque; narrative; inserted short story; first-person novel; aesthetics of diversity